STUDY ON COOLING TOWER GEOMETRY MODIFICATION FOR PERFORMANCE IMPROVEMENT USING ANSYS FLUENT AND ANSYS DISCOVERY LIVE SOFTWARE - Garnando Kristian, Daniel
As one of the systems in a power plant, the cooling tower should always operate optimally according to its design conditions. But over time, the cooling tower performance has decreased. If there is a decrease in cooling tower performance, of course, it will be bad for the whole power plant system. Evaluation of cooling tower performance is needed to find out how much deterioration in cooling tower performance after operating for decades. The method used in evaluating cooling tower performance is the performance curve method and the characteristic curve method found in the ATC-105 CTI. The effectiveness value method is also used in evaluating cooling tower performance in terms of effectiveness value. Based on the performance curve method, the capability value has decreased from 107,49% to 70.06 %. Then, based on the characteristic curve method the capability value has decreased from 113,84 % to 69,11 %. Finally, based on the effectiveness value method, the cooling tower effectiveness value has decreased from 69,2 % to 60,95 %. Geometry modification is done to improve cooling tower performance. With the modification, the airflow rate in the cooling tower has increased from 627,74 kg/s to 665,61 kg/s. The increase in airflow rate causes a decrease in the temperature of the water exiting the cooling tower from 30 °C to 29,6 °C. In the end, the decrease in the temperature of the water coming out of the cooling tower can improve the cooling tower performance in terms of the effectiveness value from 60,95 % to 62,17 %.